Configuration and Kinematics of a 3-DOF Generalized Spherical Parallel Mechanism for Ankle Rehabilitation - Jianjun Zhang; Shuai Yang; Chenglei Liu; Xiaohui Wang; Shijie Guo (Chinese Journal of Mechanical Engineering, 2024)
Abstract The kinematic equivalent model of an existing ankle-rehabilitation robot is inconsistent with the anatomical structure of the human ankle, which influences the rehabilitation effect. Therefore, this study equates the human ankle to the UR model and proposes a novel three degrees of freedom (3-DOF) generalized spherical parallel mechanism for ankle rehabilitation. The parallel mechanism has two spherical centers corresponding to the rotation centers of tibiotalar and subtalar joints. Using screw theory, the mobility of the parallel mechanism, which meets the requirements of the human ankle, is analyzed. The inverse kinematics are presented, and singularities are identified based on the Jacobian matrix. The workspaces of the parallel mechanism are obtained through the search method and compared with the motion range of the human ankle, which shows that the parallel mechanism can meet the motion demand of ankle rehabilitation. Additionally, based on the motion-force transmissibility, the performance atlases are plotted in the parameter optimal design space, and the optimum parameter is obtained according to the demands of practical applications. The results show that the parallel mechanism can meet the motion requirements of ankle rehabilitation and has excellent kinematic performance in its rehabilitation range, which provides a theoretical basis for the prototype design and experimental verification.